TECHNOLOGIES FOR DEVELOPING PROFESSIONAL COMPETENCIES OF FUTURE ENGINEERS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Sultanova Yulduzoy Abdusalomova (Uzbekistan Open Conference, 2025)
The article examines the technology of developing professional competence of future engineers in a digital educational environment, and discusses the requirements for creating a digital educational environment in the training of future engineers, ways to introduce new professional qualities into the forms of education used in the digital environment, as information and communication technologies develop, as well as ways to develop qualified teachers of the future.
Keywords: education; digital technologies; engineer; digital environment; communication; integration; design